Das weltweite Medizinernetzwerk Aufklärung gegen Tabak: ehrenamtliche Prävention made in Germany = The global medical network Education Against Tobacco - voluntary tobacco prevention made in Germany - Brinker, Titus Josef; Haney, Caelán Max (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Smoking is the leading preventable cause of premature death in Germany. The network “Education Against Tobacco” (EAT) is an initiative that was founded in Germany in 2012, in which more than 3500 medical students and physicians engage in volunteer work in about 80 medical faculties in 14 countries. In this article, the concept, activities, objectives and associated research studies oft he EAT initiative are introduced.On the school level, the initiative addresses 10- to 15-year-old secondary school students. In addition to a multimodal approach, school visits use modern media such as facemorphing apps, which are not only used by students (45,000 per year in 14 countries), but by a total of over 500,000 other people as well. The effectiveness of the school-based intervention is currently being investigated in randomised long-term studies with 20,000 adolescents in Germany. A first long-term study demonstrated evidence of a protective effect regarding the onset of smoking, especially among female students, students having a low level of education and students with a migratory background.The programme educates several hundred prospective physicians at 13 (of 28 participating) German medical faculties each year in science-based elective courses for the well-established smoking cessation counselling of patients and sensitises them to the tobacco epidemic. The approved members engage in dialogue with local members of the German house of representatives as “Ärzteverband Tabakprävention”.EAT motivates the prospective generation of physicians, initially through prevention in school settings, to face the challenge of national tobacco control at the university and federal level.
Gesehen am 12.09.2019
Artikel in deutscher, Zusammenfassung in deutscher und englischer Sprache